Four major sequence elements of simian virus 40 large T antigen coordinate its specific and nonspecific DNA binding. - Simmons, D T (1990)
By mutational analysis, we have identified a motif critical to the proper recognition and binding of simian virus 40 large tumor antigen (T antigen) to virus DNA sequences at the origin of DNA replication. This motif is tripartite and consists of two elements (termed A1 and B2) that are necessary for sequence-specific binding of the origin and a central element (B1) which is required for nonspecific DNA-binding activity. Certain amino acids in elements A1 (residues 152 to 155) and B2 (203 to 207) may make direct contact with the GAGGC pentanucleotide sequences in binding sites I and II on the DNA. Alternatively, these two elements could determine the proper structure of the DNA-binding domain, although for a number of reasons we favor the first possibility. In contrast, element B1 (183 to 187) is most likely important for recognizing a general structural feature of DNA. Elements A1 and B2 are nearly identical in all known papovavirus T antigens, whereas B1 is identical only in the closely related papovaviruses simian virus 40, BK virus, and JC virus. In addition to these three elements, a fourth (B3; residues 215 to 219) is necessary for the binding of T antigen to site II but not to site I. We propose that additional contact sites on T antigen are involved in the interaction with site II to initiate the replication of the viral DNA.